Análisis de los factores naturales y antrópicos que inciden en los accidentes de tránsito caso: sector cruz del arenal – Guaranda en la provincia Bolívar, período enero – octubre 2022. - Aroca Chimborazo, Adriana Michael (2023)
The case study refers to the factors involved in the occurrence of traffic accidents on the Guaranda - Ambato road to the Cruz del Arenal sector, for this we [XVII] call traffic accidents as an unexpected event in which different factors are involved, these events bring with them a number of consequences such as physical - psychological damage and economic losses. A series of concepts that will help a better approach to the subject are also exposed, among which are the main characteristics of the section of the Guaranda - Ambato road, to the Cruz del Arenal sector, various concepts on types of accidents, traffic signs and their classifications, some regulations and laws set forth by the National Transit Agency and the Constitution of Ecuador. The research was conducted with a qualitative approach using interviews as a technique for collecting information applied to a population selected at the convenience of the researcher. Based on the results, we identified the sectors in which a greater number of traffic accidents occur, also determining the causal factors that affect a road accident. With the analysis of the objectives achieved, three types of measures (preventive, corrective and adaptive) were proposed for risk reduction strategies in accordance with each factor identified. Key words: Road accidents, risk factors, risk reduction, prevention.